Disintegration of protein microbubbles in presence of acid and surfactants: a multi-step process. Issue 32 (28th August 2015) - Rovers, Tijs A. M.; Sala, Guido; van der Linden, Erik; Meinders, Marcel B. J.
<x xml:space="preserve">Abstract</x> In this manuscript we investigated the stability of microbubbles upon addition of surfactants (especially SDS) and acid. We related the stability of the microbubbles to physical processes.